PENGARUH PROGRAM PEMUTIHAN PAJAK KENDARAAN BERMOTOR, PEMBEBASAN BEA BALIK NAMA KENDARAAN BERMOTOR, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (Studi Kasus Pada Kantor Bersama Sistem Administrasi Manunggal Satu Atap (SAMSAT) Kabupaten Brebes) - Rahayu, Cinti; Amirah, Mrs. (PERMANA, 2018)
This study aims to prove the influence of program pemutihan motor vehicle tax (PKB), free transfer of name (BBNKB), and socialization taxation to the taxpayer to pay motor vehicle tax SAMSAT office Brebes. The population of this study are all motor vehicle texpayers registered at SAMSAT Brebes Joint Office. This sample used in this research is accidental sampling method is the technique of determining the sample by chance, ie anyone who by chance met with the researchers. Data were collected by survey method with questionnaires, and questionnaires were eligible for 100 questionnaires. Data analysis technique used Multiple Linear Regression Analysis. The results showed partialy had an affect that program pemutihan motor vehicle tax (PKB) with significant value 0,000 < 0,005, free transfer of name (BBNKB) with significant value 0,013 < 0,05,and socialization with significant value 0,000 < 0,05. Simultaneously all variabels had an effect on taxpayer to pay motor vehicle tax at SAMSAT Brebes Joint Office with significant value 0,000 < 0,05.Keywords: program pemutihan motor vehicle tax, free transfer of name, sosialization taxation, taxpayer compliance.